Aplicación móvil para la detección de somnolencia de un conductor aplicando visión artificial. - Torres Berrú, Yeferson Mauricio. (2016)
This work involves the development of a mobile application for detecting drowsiness of a driver using artificial vision, based specifically on the state of the eyes; the application uses the native mobile device camera normally working in conditions of natural light that is not working in darkness. It is oriented vehicle drivers are professionals or not, but with special emphasis on public transport where it is more likely that a driver because of the hours worked this drowsiness. The application has the ability to adapt to different drivers, works in real time and generates an index of sleepiness to be greater than 80% sounds an audible alert chosen by the user